Dynamic mathematical model as a tool for detecting and preventing school violence: a case report - Hernando, Inmaculada; Sanz, Roberto; Moreno-Latorre, Esther (Frontiers in Education, 2023)
Currently, coexistence is an essential factor that influences educational quality. Issues relating to school violence affect a large number of students, affecting their personal, academic, and professional futures. For this reason, this study aimed to present a different study tool that would allow the optimization of the factors that influence classroom climate, establish mechanisms to detect and predict how the modification of these factors can positively or negatively affect it, and determine the most appropriate intervention before it occurs. Dynamic mathematical models are complex tools that allow us to study a given problem or reality in real-time and develop predictive instruments through the analysis of mathematical relationships, allowing us to adapt the answers in a customized manner. In this study, an example is provided in measuring classroom climate throughout an academic course in a simulated situation. It consists of a dynamic mathematical model developed with Stella 10.0 software using only some of the variables that affect classroom climate, which are distributed in two sections—a psychological one that includes Rabies Level and Isolation Level due to loss of self-esteem and a physical one that includes the number of aggressive students and the total number of physically assaulted students. Since the classroom climate is very complex, other variables or a greater number of them could have been used in this hypothetical case; however, the example explains how this kind of model works and shows the great utility that it can have in this type of study. Regarding the most significant benefits that this tool can offer, some stand out. On the one hand, we can adapt the instrument to the specific characteristics of a class group, introducing or eliminating the variables depending on their relevance to the problem at hand. On the other hand, this versatile tool not only adapts to the reality of the classroom but also to the specific moment in which the students are. The greatest limitation of a Dynamic Mathematical Model as a tool is the large quantity of information required to adjust the model to reality; the more information we have, the more adjusted the model can be. Furthermore, gathering the type of information needed to develop the model is complicated.